The Efficacy of Comprehensive School Health Course in Changing Pre-Service Teachers' Attitudes and Reactions Toward Weight-Related Teasing. (September 2021) - Saunders, Jessica F.; Nutter, Sarah; Brun, Isabel; Exner-Cortens, Deinera; Russell-Mayhew, Shelly
Teachers view overt expressions of weight stigma, such as weight-related teasing, as troublesome but are often ill-prepared to address instances of weight-related teasing when they arise in the classroom. Comprehensive school health is an emerging framework that aims to better prepare teachers to address issues of health and wellness in the classroom, including weight-related teasing. We examined the efficacy of a university course in comprehensive school health in changing pre-service teachers' attitudes and perceptions of weight-related teasing. Pre-service teachers read a vignette and responded to 10 items about the vignette at both the beginning and end of the semester-long course. Items relating to pre-service teachers' perception of, responsibility and obligation to address the weight-related teasing event showed significant, positive change from the beginning to end of the semester. These results suggest that exposure to developmentally sound methods of delivering health-related content can support adaptive educator reactions to weight-related teasing.